Realizarea Agendei 2030 prin cheltuieli publice responsabile - Ulian, Galina; Năstase, Carmen-Eugenia (CEP USM, 2023)
The article focuses on sustainable public procurement with respect to its environmental ramifications and its potential in addressing social issues. Drawing on an array of scientific research, reports from international bodies, and legislative documents, alongside a review of global practices in sustainable procurement, the authors articulate the various reasons why public procurement is pivotal to sustainable development. They delve into the necessary legislative and policy frameworks that underpin procurement activities and the financial mechanisms that support them. Key to the successful enactment of sustainable procurement are the political determination, the business and stakeholder recognition of its benefits, and the backing from governmental entities in terms of both fiscal and methodological guidance, as well as informational support for those engaged in public procurement.
Keywords: sustainable development; sustainable public procurement; financing